Meningkatkan Kosakata Bahasa Inggris dengan Kegiatan Literasi, Sosialisasi Anti-Bullying dan Pembuatan Konten Edukatif di Panti Asuhan El – Ministry Palangka Raya - Maida Norahmi; Rikha Aderia; Roy Saputro Wijoyo; Salma Azzahra; Sela Eninta BR Kaban (Yayasan Literasi Sains Indonesia, 2026)
This community service program was implemented with the main objective of improving children’s literacy and English vocabulary skills while promoting anti-bullying values at El-Ministry Orphanage in Palangka Raya. The program was designed as a collaborative effort between the implementation team and the orphanage to address the limited educational resources, particularly in foreign language learning and character development. The program was conducted in two sessions consisting of three main activities: (1) English literacy practice, (2) socialization and education on anti-bullying values, and (3) creative content production based on vocabulary learning. During the literacy and socialization sessions, children were encouraged to participate actively through discussions, storytelling, role-play, and interactive quizzes that combined learning with entertainment. The creative content activity focused on vocabulary memorization and enrichment using a gamification approach, allowing children to learn through play and healthy competition. The results indicate a noticeable improvement in children’s ability to recognize and use basic English vocabulary, along with increased awareness of empathy, tolerance, and anti-bullying values. Overall, this initiative generated positive educational and social impacts, emphasizing the importance of community service programs that integrate literacy enhancement and character education to support children’s growth and development in orphanage environments.